Designing and psychometric evaluation of the nursing instructors clinical leadership style scale (CLSS): a sequential exploratory mixed-methods design - Moluk Pouralizadeh; Abbas Ebadi; Ehsan Kazemnezhad Leyli; Ali Bazzi (BMC Nursing)
Abstract Background Effective leadership in clinical nursing education is crucial for shaping competent practitioners and ensuring quality patient care. Despite its importance, there is no psychometrically validated instrument specifically designed to assess leadership styles in this context. This study aimed to develop and validate the Clinical Leadership Style Scale (CLSS), a tool for measuring leadership styles in clinical nursing education. Methods A sequential exploratory mixed-methods design was employed with Iranian participants in three phases. Initial item generation was informed by a systematic review (25 articles, 1974–2024) and qualitative content analysis of interviews with 11 stakeholders (faculty, students, administrators). An initial pool of 57 items was created based on these findings and a review of 30 existing instruments. The scale was refined and validated with 522 nursing students through face validity, content validity (CVR > 0.56, κ > 0.75), item analysis (α = 0.87), exploratory factor analysis (KMO = 0.943), and confirmatory factor analysis (CFI = 0.97, RMSEA = 0.094). Results The final 35-item CLSS measures three leadership styles: Dynamic Leadership (α = 0.96), Dysfunctional Authoritative Leadership (α = 0.93), and Systematic-Static Leadership (α = 0.78). The scale demonstrated strong internal consistency (α/Ω = 0.78–0.97), test-retest reliability (ICC = 0.88–0.92), and discriminant validity (HTMT < 0.37). A negative correlation was observed between Dynamic and Dysfunctional Authoritative styles (r = − 0.72), and a positive correlation between Dynamic and Systematic-Static styles (r = 0.58). Conclusion The CLSS is a reliable and valid instrument for evaluating leadership styles in clinical nursing education. It can support faculty development, promote positive leadership behaviors, and enhance educational outcomes.